Comparison between Outcome of Wedge Excision of Perforation Site and Trimming of Perforation Margin Followed by Primary Repair in the Management of Ileal Perforation - Ullah, Md Aziz; Rahman, Soma (Medicine Today, 2017)
The aim of this study is to compare between the outcome of wedge excision of perforation site and trimming of perforation margin followed by primary repair in the management of ileal perforation in selected patients. This is an observational study with data from department of Surgery, Sir Salimullah Medical College and Mitford Hospital during February, 2007 to July, 2010. The study included 108 patients of ileal perforation of 15-67 years of age. All patients were treated by primary repair after either wedge excision of perforation site (Group I) or trimming of perforation margin (Group II). Perforation due to typhoid is common in both groups. Abdominal pain, fever, abdominal distention, constipation and vomiting were more frequent in both groups of patients. Signs of peritonitis were observed almost all the patients. Pneumoperitoneum was found 77.8% in group I and 66.7% in group II in X-ray. In ultrasonography ascitis and distended bowel loop was found 44.4% in group I and 66.7% in group II. Typhoid, tuberculosis, nonspecific ulcer and chronic nonspecific ulcer were found in histopathology. Post-operative complications were more in group II. Anastomotic leakage was found 18.5% in group I and 38.9% in group II. Prolonged ileus was observed 16.7% in group I and 33.3% in group II. Anastomotic leakage and Prolonged ileus difference were statistically significant (p<0.05). The mean duration of hospital stay was significantly (p<0.05) higher in group II, where the mean(±SD) duration of hospital stay was 14.2±7.2 days in group I and 18.1±8.9 days in group II. Mortality was observed 9.3% only in group II. So Wedge excision followed by primary repair is better in terms of post operative mortality and morbidity in the management of ileal perforation in selected patients. Medicine Today 2017 Vol.29(2): 17-20